Tarbiyah-Based Student Mental Health Support Model for Promoting Learning Well-Being in Islamic Boarding Schools - Muhammd Abduh; Jaziela Huwaida; Cecep Sobar Rohmat; Ahsanti Asti Nurul Izzati; Pervin Çapraz (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
Students' mental health is a critical factor in fostering learning well-being within Islamic boarding schools (pesantren). However, existing studies predominantly conceptualize mental health as an individual psychological issue and have paid limited attention to tarbiyah-based mentoring as an integral component of the pesantren educational system. This study aims to explore a tarbiyah-based mental health support model for students and examine its contribution to enhancing learning well-being at Pondok Modern Assalam Sukabumi. This research employed a qualitative case study design. Data were collected through semi-structured interviews, participant observation, and document analysis involving the head of the boarding school, student affairs officers, homeroom teachers, mudabbir (dormitory mentors), dormitory administrators, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through the processes of open coding, axial coding, and selective coding. The findings reveal that the mental health support model is implemented through a multi-layered mentoring system involving mudabbir, homeroom teachers, the student affairs division, and school leaders. This model integrates tarbiyah values, social support, character development, and Islamic spirituality into promotive, preventive, curative, and community-based intervention strategies. The implementation of this model contributes to five indicators of learning well-being: inner peace, increased learning motivation, improved academic achievement, healthy social relationships, and stronger discipline and adherence to pesantren values. This study proposes a Tarbiyah-Based Student Mental Health Support Model as a conceptual framework that enriches mental health scholarship in Islamic education and offers an alternative approach for developing mental health services in residential educational institutions.